A new cave-dwelling species of the alpheid shrimp genus Salmoneus Holthuis, 1955 (Crustacea: Decapoda: Caridea) from the Ryukyu Islands, southern Japan - Komai, Tomoyuki; Yamada, Yusuke; Yunokawa, Kyo (Zootaxa, 2015)
A new species of the alpheid shrimp genus Salmoneus Holthuis, 1955, S. antricola n. sp., is described and illustrated on the basis of a single ovigerous specimen from an aphotic marine cave at a depth of 12 m, off Ie Island, Okinawa Islands, the Ryukyu Archipelago. It is morphologically similar to five species presently referred to the S. jarli (Holthuis, 1951) species group: S. erasimorum Dworschak, Anker & Abed-Navandi, 2000, S. komaii Anker, 2011, S. paulayi Anker, 2011, S. poupini Anker, 2011, and S. sketi Fransen, 1991. However, the minor cheliped with an elongate carpus being subequal to the chela, the lack of teeth on the cutting edges of the minor cheliped fingers, and the very slender third to fifth pereopods are obvious characters that distinguish S. antricola n. sp. from all of its presumed close relatives. Among the 50 species of Salmoneus, only S. sketi and the present new species are known from marine caves.